MEMBANGUN: “BATTLE DRONE” COMPUTERIZED TRADING CARD GAME - Reza Andrea; Addy Suyatno; Indah Fitri Astuti (Mulawarman University, 2013)
One of the popular and very famous game is trading card game (collectible card game), the game collect and play cards, trade the cartoon figures cards, monster or super hero. Trading card game’s cards are not only for collected but also can be played with some game rule and strategy. Usually people play trading card game with manualy system without any computer system, and finally “Battle Drone” computerized trading card game was created. This game focuse on strategy to construct the deck and victory calculation. Developed use Water fall system, that contain system analyst, design, coding, testing, and maintenance. It was created by using SwishMax, with supported application CorelDraw and Cool Edit Pro. A computerized trading card game that use system barcode as connection between cards and interface software.